Genetic characteristics of competitive swimmers: a review - Ben-Zaken, Sigal; Eliakim, Alon; Nemet, Dan; Kaufman, Leonid; Meckel, Yoav (Biology of Sport, 2022)
A successful swimming performance is a multi-factorial accomplishment, resulting from a complex interaction of physical, biomechanical, physiological and psychological factors, all of which are strongly affected by the special medium of water as well as by genetic factors. The nature of competitive swimming is unique, as most of the competitive events last less than four minutes. Yet training regimens have an endurance nature (many hours and many kilometres of swimming every day), which makes it impossible to classify swimming by definitions of aerobic-type or anaerobic-type events, as in track and field sports. Therefore, genetic variants associated with swimming performance are not necessarily related to metabolic pathways, but rather to blood lactate transport (MCT1), muscle functioning (IGF1 axis), muscle damage (IL6) and others. The current paper reviews the main findings on the leading 12 genetic polymorphisms (located in the ACE, ACTN3, AMPD1, BDKRB2, IGF1, IL6, MCT1, MSTN, NOS3, PPARA, PPARGC1A, and VEGFR2 genes) related to swimming performance, while taking into consideration the unique environment of this sport.